The effect of jigsaw cooperative learning strategy on fourth graders' achievement in teaching EFL at Qalqilya City / Enas A. A. Abuhamda, Ramiaida Darmi and Hazlina Abdullah - Abuhamda, Enas A. A; Darmi, Ramiaida; Abdullah, Hazlina (Bahagian Penyelidikan dan Jaringan Industri, UiTM Cawangan Melaka, 2020)
This study aimed at investigating the effect of jigsaw cooperative learning strategy on the fourth graders' achievement in teaching EFL at Qalqilya city. The study examined the effect of the following variables: gender, academic qualifications and years of experience on Palestinian fourth graders' achievement. To achieve the purpose of the study, the researcher developed one tool: a 21item questionnaire. The researcher distributed the questionnaire randomly on a sample of 29 Palestinian fourth graders' English language teachers in Qalqilya city. A quantitative method was used to analyze the collected data. The collected data were analyzed and treated statistically using SPSS. The results of the study showed that Palestinian fourth graders’ have positive attitudes towards using jigsaw cooperative learning strategy as a tool of teaching EFL. In the light of the results of the study recommended that teachers should avoid merely using lecture method in teaching EFL for the fourth graders that leads for poor participation and poor understanding of the concepts. Schools teachers should concentrate on teaching techniques or teaching methods like jigsaw strategy, which will enable pupils to understand properly the concepts taught in class. In addition, it suggested that further researches should be conducted on the effect of jigsaw cooperative learning strategy on different English skills and other school subjects.